Honey Stick Original / Nurul'aliah Adiba Azmi - Azmi, Nurul'aliah Adiba (2021)
Honey Stick Original is a business located in Petaling Jaya dedicated to producing sustainable, high quality honey that is pure, natural, and non-pasteurized. We sell our honey through farmer's markets, online, wholesalers and retailers. We are differentiated through our locally unique types of honey and selling our bees post honey season to groves to help pollinate their crops. With these differentiated points we intend to expand our business further with our current customers as well as developing untapped segments. We aim to increase our brand awareness by increasing our social media presence. Our company aims to expand our distribution network to include more organic and local stores. This will help us reach our goal to increase our business-to-business sales.